Simple synthesis of nanosheets of rGO and nitrogenated rGO - Pallellappa Chithaiah; Madhan Mohan Raju; Giridhar U. Kulkarni; C. N. R. Rao (Beilstein Journal of Nanotechnology, 2020)
A green and facile approach has been developed for the large-scale synthesis of nanosheets of reduced graphene oxide (rGO) and nitrogenated reduced graphene oxide (N-rGO). This has been achieved by direct thermal decomposition of sucrose and glycine at 475 °C in ca. 7 minutes, respectively. The present protocols for synthesizing rGO and N-rGO are simple and environmentally friendly as we do not use any harmful reagents, metal catalysts and solvents. Along with that, this method offers an inexpensive route with high yields to prepare rGO with a high nitrogen content (20–25 atom %). To further improve the properties of the synthesized rGO sheets, hydrogen treatment has been carried out to reduce the oxygen functional groups. Cyclic voltammograms and charge–discharge experiments have been carried out to understand the supercapacitor behavior of rGO and hydrogen treated (H-rGO) samples.